Risk and Reward The Science of Casino Blackjack - Werthamer, N. Richard (Springer International Publishing, 2018)
Praise for the First Edition: "As the title suggests, Risk and Reward: The Science of Casino Blackjack is a book about strategies for increasing your chances of winning the game of Blackjack. ... The author makes the book accessible to a variety of audiences by presenting the strategies separately from the mathematical analysis. ... It is well organized, flows nicely and cites previous works. ... Overall, the book is an entertaining and stimulating read for both mathematicians and casino goers." -- Michael Rowell, The Mathematical Association of America, 2009 For decades, casino gaming has been steadily increasing in popularity worldwide. Blackjack, among the usual casino table games, is the only one where astute choices of playing strategy can create an advantage for the player. Risk and Reward analyzes the game in depth, pinpointing not just its optimal strategies but also its financial performance, in terms of both expected cash flow and associated risk. This Second Edition begins by laying out the strategies and their performance in a clear, descriptive style. The presentation is self-contained, non-mathematical, and accessible to readers at all levels of playing skill, from novice to expert. Careful attention is also given to simplified but still nearly optimal strategies that are easier to use in a casino environment. Unlike other books in the literature, each aspect of the strategy is derived mathematically, to justify its claim to optimality. The derivations mostly use algebra and calculus, although some require more advanced analysis detailed in appendices. For easier comprehension, formulae are translated into tables and graphs, many of which are linked to interactive versions on the author's website that recompute for each reader's choice of playing conditions. Risk and Reward will appeal to everyone interested in blackjack: every player seeking to improve their performance as well as those with training in mathematics and intrigued by its application to a game they enjoy. N. Richard Werthamer is retired from a successful career as a scientist and executive, most recently as the Executive Officer of the American Physical Society. He graduated summa cum laude from Harvard College before receiving his PhD in Theoretical Physics from the University of California at Berkley. His original research has been published extensively in the world's leading journals. In this book, he applies his scientific background to the analysis of blackjack.